MAKNA PUASA DALAM PEMBENTUKAN KONTROL DIRI ANAK MI: TINJAUAN PSIKOLOGI ISLAM DALAM PERSPEKTIF PENGKAJIAN ISLAM - Okta Vitriani; Ahmad Arifi (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2026)
Character education at the Madrasah Ibtidaiyah (MI) level places self-control as an essential competency in supporting the academic, social, and moral development of students. Contemporary basic education challenges, such as increased exposure to technology, changes in social interaction patterns, and weak regulation of children's emotions, require an educational approach that is not only cognitive but also value- and spiritually-oriented. In the context of Islamic education, fasting is a form of worship that has both ritual and psychological-educational dimensions that have the potential to shape self-control from an early age. This study aims to examine the meaning of fasting from an Islamic perspective and its relevance to the formation of self-control in MI children through the framework of Islamic psychology. The study used a qualitative approach with a literature review design, analyzing primary Islamic sources (the Qur'an, hadith, and tafsir) as well as secondary literature in the form of Islamic psychology books and national and international journal articles from 2019 to 2024. The data were analyzed using thematic analysis to synthesize the concepts of fasting, self-control, and child development characteristics. The results of the study show that fasting can be interpreted as a means of practicing self-control, developing patience, forming discipline, and strengthening self-awareness, which are relevant to the psychological development stages of MI children, as long as it is implemented gradually and supported by a contextual pedagogical approach.